IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 63 TAHUN 2002 TENTANG HUTAN KOTA - Elvida Yosefi Suryandari; Subarudi Subarudi (Jurnal Analisis Kebijakan Kehutanan, 2014)
Indonesian Government enacted Government Regulation (PP) No. 63/2002 concerning  urban forest. However, its field implementation performance on the average is below 10%. Constraints are identified, i.e. policy inconsistencies and different perceptions of urban forest concept  among designers, policy makers and communities.  The purpose of the study are to identify the urban  forest related regulations, to analyze PP No. 63/2002 and to identify relevant stakeholders. This study used policy and stakeholders analyses. The results showed that several points in this regulation need to be reconsidered such as the concept of  urban forest (including layers of different plants or trees), the area and solidity requirements of urban forest, the provision of incentives and disincentives, conformity of urban forest with provincial or regent regulations and  the increase of community participation.  PP No. 63/2002 and its subsequent regulations need to be improved by the Ministry of Forestry with references to those aspects, so that it becomes implementable. Implementation of a policy depends considerably upon the contents of the policy and responses from local government. Involvement and coordination among stakeholders are needed in order to establish a sustainable urban forest.